A review on the physical & chemical properties of sea sand to be used a replacement to fine aggregate in concrete. (2022) - Soundarya, N.
Abstract: Sea sand is a widely available form of sand on comparing with the river sand. Sea sand is not used widely because it may contain chloride, sea shells in large numbers and other harmful chemicals like Fe2 O3, V2 O5, Cr2 O3, Ga2 O3, Br2 O and Re2 O7 . The usage of sea- sand may either address the concrete's existing problems in strength and durability or can be an excellent replacement material to river sand which is in great danger due to excessive excavation in almost all countries around the world. A large number of individual works have been done worldwide on sea sand as partial/full replacement of fine aggregates in concrete and this paper is aimed and compiling all the works and give an in depth understanding about how this material can be effectively utilized in concrete. The present work focuses on compiling and reporting various works on the general material properties of sea- sand, effect of chloride content in strength and workability, effect of rainfall on the chloride content, alkali – aggregate reaction. It also consists and understanding of the likely dangerous chemical components, effect of shell content on workability and strength, effect of size and uniformity of sea sand in concrete. Effect on compressive strength due to grading of the sea sand's, curing with sea water and using washed the sea sand before use have also been reported. From the report it can be concluded that by understanding the material properties of sea- sand, it can be effectively utilized as fine aggregate in concrete.